2001
DOI: 10.1136/heart.86.5.527
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of atrial fibrillation in acute myocardial infarction: the GISSI-3 data

Abstract: Background-Atrial fibrillation is the most common supraventricular arrhythmia in patients with acute myocardial infarction. Recent advances in pharmacological treatment of myocardial infarction may have changed the impact of this arrhythmia. Objective-To assess the incidence and prognosis of atrial fibrillation complicating myocardial infarction in a large population of patients receiving optimal treatment, including angiotensin converting enzyme (ACE) inhibitors. Methods-Data were derived from the GISSI-3 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
190
6
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(230 citation statements)
references
References 26 publications
26
190
6
8
Order By: Relevance
“…[6][7][8] Therefore, it is certain that AF is associated with an increased in-hospital mortality after AMI in both the prethrombolytic and thrombolytic eras. 1,[6][7][8][9][10] In the present study, we found that patients with AF have significantly higher incidences of stroke, advanced CHF, advanced Killip score upon presentation, more myocardial damage, notably lower LVEF, and more advanced age than those with sinus rhythm. An important fact is that AF patients had a remarkably lower incidence of successful reperfusion and markedly higher 30-day mortality than those with sinus rhythm undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Therefore, it is certain that AF is associated with an increased in-hospital mortality after AMI in both the prethrombolytic and thrombolytic eras. 1,[6][7][8][9][10] In the present study, we found that patients with AF have significantly higher incidences of stroke, advanced CHF, advanced Killip score upon presentation, more myocardial damage, notably lower LVEF, and more advanced age than those with sinus rhythm. An important fact is that AF patients had a remarkably lower incidence of successful reperfusion and markedly higher 30-day mortality than those with sinus rhythm undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…5) As compared with AMI patients with normal sinus rhythm, AMI patients with new-onset AF have been shown to have worse baseline characteristics, more complicated hospital courses, and unfavorable clinical outcomes such as higher incidences of advanced congestive heart failure (CHF), cardiac embolic stroke, and mortality. 1,[6][7][8][9][10]) Surprisingly, all of these studies were conducted in the prethrombolytic or thrombolytic eras. 1,[6][7][8][9][10] Evidence-based medicine has demonstrated that primary percutaneous coronary intervention (PCI) is superior to thrombolytic therapy in terms of increasing the successful reperfusion rate, reducing the incidences of recurrent ischemia and reinfarction, and improving prognostic outcome in patients with acute ST-segment elevation myocardial infarction (STEMI).…”
Section: T He Incidence Of New-onset Atrial Fibrillation (Af) Is Re-mentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation is a well-known poor prognostic marker of both short-and long-term mortality in acute MI. 9,22 In this study, the increase in in-hospital mortality was clearly attributed to an increase in the free-wall rupture rate. Whether uncomplicated atrial infarction per se increases short-term mortality is unknown.…”
Section: Discussionmentioning
confidence: 51%
“…In the TRACE trial,38 a lower risk of new‐onset AF was observed among patients discharged with trandolapril. In contrast, the Gruppo Italiano per lo Studio Della Sopravvivenza Nell'Infarto Miocardico‐3 (GISSI‐3) trial39 reported no significant reduction in the risk of new‐onset AF with RAS inhibition. In a meta‐analysis including these 2 trials, no association was observed between RAS inhibition and risk of new‐onset AF in a subgroup of post‐AMI patients 40.…”
Section: Discussionmentioning
confidence: 98%